REDUCING THE DRAG ON A CIRCULAR CYLINDER BY UPSTREAM INSTALLATION OF CYLINDER TYPE-I AND DOWNSTREAM INSTALLATION OF ELLIPSE CYLINDER - Hakam, Amirul; Imron, Chairul; Widodo, Basuki; Yuwono, Tri Yogi (MATTER: International Journal of Science and Technology, 2018)
Various forms and number of passive control have been investigated in order to minimize the drag coefficient received by circular cylinder. Thus, the strength of circular cylinder construction can be maintained longer. In this study, a circular cylinder with two passive controls are the first passive control fix be a cylindrical type-I is placed in front of the cylinder at distance ratio with difference 0.6, while the second passive cylinder compares the ellipse and horizontal type I which is placed behind the cylinder at a ratio of distance with difference 0.3. The flow across the circular cylinder with two passive controls in Reynolds 5000 is solved by numerically using the first order finite difference method with the third order error and second order finite difference method with second order error. Differences of second passive control geometry and variation of distance of S / D and T / D have effect on drag coefficient obtained. The minimum drag coefficient is obtained at the distance S / D = 1.8 and T / D = 1.5, using second passive control of the ellipse or horizontal type I cylinder. However, the comparison results that the second passive control of the elliptical shape minimizes the drag coefficient by up to 39% against the cylinder without control. Mathematical model of drag for circular cylinder with passive controls cylinder type I and ellipse is . This model can be used to find the drag coefficient on S/D and T/D directly and easier.